Bone mineral density and osteoporosis related risk factors in type 2 diabetes mellitus - Nugroho, Heri; Kurniawan, Rizal; Purnami, Cahya Tri (International Journal of Public Health Science (IJPHS), 2024)
Diabetes mellitus negatively affects bone tissue and unfavourably impacts bone mineral density (BMD), therfore increasing the probability of fractures through pathological mechanisms. This study aimed to explore the factors associated with BMD and osteoporosis risk in individuals with a diagnosis of type 2 diabetes mellitus (T2DM). An investigation was undertaken involving 49 patients diagnosed with T2DM who fulfilled the specified criteria. These individuals underwent BMD assessment as part of a cross-sectional study. The analysis encompassed both univariate and bivariate approaches, utilizing the Chi-square test (X2) and binary logistic regression methods. A total of 30 participants (61%) have decreased BMD. Among the participants aged 60 years and above, 83.4% exhibited a decreased BMD status (osteopenia and osteoporosis), in contrast to the under 60 years age group, in which 40% displayed decreased BMD status. Older age (>60 years) is a risk factor for decreasing bone density onset of diabetes mellitus (DM) diagnosis, duration of DM, glycemic control, body mass index (BMI), use of thiazolidinediones (TZD) drugs, kidney function, were not associated with lower BMD in T2DM patients.